2009
DOI: 10.1002/gps.2255
|View full text |Cite
|
Sign up to set email alerts
|

The association between different cognitive domains and age in a multi‐centre study of middle‐aged and older European men

Abstract: Our data suggest that although a proportion of the variance in cognitive function among European men is explained by individual level differences, a significant proportion is due to contextual phenomenon. Such contextual factors need to be considered when analysing multi-centre data and European men should not be treated as homogeneous when assessing cognitive performance using existing instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…As reported previously, there were significant betweencentre differences in cognitive test scores with centres in northern and western Europe (Leuven, Manchester, Malmö) scoring highest for all the tests, while centres in Southern Europe scored lower (34). All four scores were inversely associated with higher age (34).…”
Section: Cognitive Testssupporting
confidence: 78%
See 2 more Smart Citations
“…As reported previously, there were significant betweencentre differences in cognitive test scores with centres in northern and western Europe (Leuven, Manchester, Malmö) scoring highest for all the tests, while centres in Southern Europe scored lower (34). All four scores were inversely associated with higher age (34).…”
Section: Cognitive Testssupporting
confidence: 78%
“…All four scores were inversely associated with higher age (34). The distribution of the FC z-score is shown in Fig.…”
Section: Cognitive Testsmentioning
confidence: 90%
See 1 more Smart Citation
“…Also, the odds of lower cognitive function were higher when the number of unhealthy behaviours was repeated over time (across three different waves) [89]. Similar findings from the Suwon Longitudinal Ageing Study (SLAS) showed that a combination of multiple positive lifestyle behaviours (such as non-smoking, vegetable consumption and social activity) was associated with the higher cognitive ability [90]. However, since these behaviours tend to cluster [91,92], the extent to which apparent effects of one behaviour were attributable to (i.e.…”
Section: The Role Of Lifestyle Behaviours On Cognitive Ageingsupporting
confidence: 53%
“…A five-point-lower DSST score increased the risk of HMA by 13% and recurrent HMA to an even greater degree after considering other factors. To put this in context, ~40 g alcohol (3–4 standard drinks) will acutely lower an individual’s DSST score by approximately five points (2123), and among people in the same age range as those in ACCORD-MIND, a one-point difference in DSST score is consistent with the difference in cognition seen between two people differing in age by 1–2 years (2428), differing in formal education experience by ~4 years (26) and, among people with type 2 diabetes, differing in A1C by 0.57% (16). Thus, even small differences in cognition can have an impact on hypoglycemia risk.…”
Section: Discussionmentioning
confidence: 76%